The Role and Place of Information and Communication Technologies in the Formation of Professional Competencies of Higher Education - Шабельник, Тетяна Володимирівна; Шабельник, Т. В.; Шабельник, Татьяна Владимировна; Shabelnyk, Tetiana V.; Ротаньова, Наталія Юріївна; Ротаньова, Н. Ю.; Ротанёва, Наталия Юрьевна; Rotanova, Nataliia Yu.; Дяченко, Оксана Федорівна; Дяченко, О. Ф.; Дяченко, Оксана Федоровна; Diachenko, Oksana F.; et al. (Medknow Publications and Media Pvt. Ltd., 2020)
The article discusses the concept of a student's ICC, which is considered as the most important characteristic of professional competence, which includes a combination of the following components: motivational-value (orientation of the student's personality to the development of his ICC in future professional activity); technological (complex of skills and abilities of ICC-activity); cognitive (a system of knowledge of modern technologies of future professional activity); is defined, that pedagogical support for the formation of ICC of future specialists is an individualization of the learning process of students, due to their personal and professional needs and the specifics of a regional university, providing the necessary conditions for the implementation of this process.

У статті розглядається концепція ІКК (інформаційно-комунікативної компетентності) студента, яка розглядається як найважливіша характеристика професійної компетентності, що включає поєднання таких компонентів: мотиваційно-ціннісний (орієнтація особистості студента на розвиток його ІКК у майбутній професійній діяльності); технологічний (комплекс умінь та навичок ІКК-діяльності); когнітивний (система знань про сучасні технології майбутньої професійної діяльності); визначено, що педагогічна підтримка формування ІКК майбутніх спеціалістів полягає в індивідуалізації освітнього процесу студентів, враховуючи їхні особисті та професійні потреби та специфіку регіонального університету, забезпечуючи необхідні умови для реалізації цього процесу.

В статье рассматривается понятие ИКК (информационно-коммуникационная компетентность) студента как важнейшая характеристика профессиональной компетентности, включающая в себя совокупность следующих компонентов: мотивационно-ценностный (ориентация личности студента на развитие его ИКК в будущей профессиональной деятельности); технологический (комплекс навыков и умений ИКК-деятельности); познавательный (система знаний о современных технологиях будущей профессиональной деятельности). Определено, что педагогическим обеспечением формирования ИКК будущих специалистов является индивидуализация образовательного процесса студентов, обусловленная их личными и профессиональными потребностями и спецификой регионального вуза, обеспечивающая необходимые условия для реализации этого процесса.
Shabelnyk T. The Role and Place of Information and Communication Technologies in the Formation of Professional Competencies of Higher Education / T. Shabelnyk, N. Rotanova, O. Diachenko, M. Netreba, L. Tonkykh, O. Tsilmak // Sys Rev Pharm. – V. 11 (10). - Medknow Publications and Media Pvt. Ltd., 2020. – Р. 890-893.
Keywords: information technology; professional competence; students; сommunication technologies; інформаційні технології; професійна компетентність; студенти; комунікаційні технології; информационные технологии; профессиональная компетенция; студенты; коммуникационные технологии; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education